A study of severely deformed austenite and transformed martensite: Texture inheritance and high-temperature fracture anisotropy. (March 2023) - Cheng, Lei; Yu, Wei; Han, Ying; Cheng, Zhicheng; Cai, Qingwu
Abstract: A kind of herringbone martensite featuring three typical texture components was achieved through severe hot rolling and subsequent quenching process. It is clarified that the activated slip planes in the deformed prior austenite grains facilitate the preferential transformation of herringbone martensite, which also contributes to the formation of martensitic textures. High-temperature tension tests revealed the herringbone martensite exhibited obvious fracture anisotropy. Initial plastic deformation of specimens processed along rolling direction is mainly dominated by the sliding of (quasi) Bain zone boundaries, while of specimens processed along transversal direction it tends to the sliding of prior austenite grain boundaries. Moreover, it is the continuous dynamic recrystallization mainly dominated the softening stage of tensile curves and the motion of geometric necessary dislocations can also be affected by slip systems even at 730 ℃. This study clarified the hereditary features of severely deformed austenite and high-temperature deformation mechanism of the transformed herringbone martensite. Graphical Abstract: ga1